1980
DOI: 10.1111/j.1365-2621.1980.tb04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Soybeans During Processing to Yield Desolventized‐toasted Meal

Abstract: Microscopic examination of conventionally processed soybeans showed that flaking was sufficient to disrupt almost all of the cotyledon cells but had little effect on protein bodies or lipid bodies. Hexane extraction changed the surface of protein bodies from smooth to granular. Desolventizing-toasting was disruptive to cell walls and caused protein bodies to agglomerate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Images obtained from scanning electron microscope and transmission electron microscope of untreated and treated soybean showed that there was noticeable cell wall disruption. (Bair and Snyder, 1980;Campbell and Glatz, 2009). With adequate cell wall disruption in pre-treated soybean (soybean meal), its protein easily dissolves into alkaline solution (Lee et al, 1983).…”
Section: Influence Of Biomass Typementioning
confidence: 96%
“…Images obtained from scanning electron microscope and transmission electron microscope of untreated and treated soybean showed that there was noticeable cell wall disruption. (Bair and Snyder, 1980;Campbell and Glatz, 2009). With adequate cell wall disruption in pre-treated soybean (soybean meal), its protein easily dissolves into alkaline solution (Lee et al, 1983).…”
Section: Influence Of Biomass Typementioning
confidence: 96%
“…Typically, soybeans are cracked into approximately 4-6 fragments per bean, conditioned at 60°C, and then passed through smoothsurfaced roller mills, resulting in flakes approximately 1 cm across by 250 lm thick [29]. Flaking cracked and conditioned soybeans causes extensive cell distortion and a high degree of disruption of cell walls with little change in morphology of the protein and oil bodies [30] as has been seen for other oilseeds, as well [31]. This disruption allows solutes and solvents to pass easily through the cellular matrix, which explains why flaking enhances hexane extraction.…”
Section: Flakingmentioning
confidence: 99%
“…CW cell wall, PB protein body, N cell nucleus, OB oil body. Copyrighted figure courtesy of the Journal of Agricultural and Food Chemistry, ACS publishing even after removing the oil [30]. In AEP, however, the removal of oil from the cells depends on the length and tortuosity of the oil release pathway.…”
Section: Flakingmentioning
confidence: 99%
“…Physical changes that accompanied the pH shift in the whole beans were studied using Scanning Electron Microscopy, according to the procedure of Bair and Snyder (1980). Procedural modifications included the omission of paraformaldehyde for the fixation step and the use of gold-palladium (60:40) to coat the samples in a vacuum evaporator.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Rockland and Metzler (1967) devised a process for quick-cooking lima beans. Bakker-Arkema et al (1967) used a drum drier and Kon et al (1974) used steam heat to produce a high quality bean product. Carvalho and Jansen (1977) and Yadav and Liener (1978) both prepared pre-cooked, instant bean products by dry roasting.…”
Section: Introductionmentioning
confidence: 99%